Finite element simulation of single fiber pullout test - Chew, Gerard Thean Poh. (2009)
This report describes the work done to develop 2 FEA models used to analyze the Single Fiber Pullout case. Since both the FBC ( Fixed Back Configuration) and the RTC ( Restrained Top Configuration ) cases were studied, two FEA models were developed, one for each test configuration. Two material sets: one with a high modulus matrix Em/Ef = 0.5 and one with a low modulus matrix, Em/Ef = 0.01 were evaluated as well.